Systematic Method of Retrofitting Wastewater Transportation Systems for Enhanced Reliability - Jean Pimentel; Ákos Orosz; Andres Castellar-Freile; Kirti Yenkie (Chemical Engineering Transactions)
While the treatment of wastewater is an important issue that received significant attention in the past decades, improving the related technologies is only one part of a more complex task. Domestic wastewater is usually transported via the city’s sewer system, and in many places, it is combined with rainwater. This means that disturbances, such as heavy rainfall or failures in the pipeline system, can lead to floods of polluted wastewater. Thus, it is important to design such transportation systems to be reliable. This work presents a methodology for generating several potential extensions to retrofit an existing water transportation network and increase its reliability. Reliability and feasibility evaluation is performed via the P-graph framework, after which the non-dominated networks are collected. Results of the presented case study show that reliability can be increased 3 times by adding only some of the possible extensions to the network. The methodology proposed analysed 512 plausible retrofitting alternatives, from which 20 are non-dominated networks. This range of alternatives provides designers with insightful information to decrease water pollution and the vulnerability of wastewater systems.